“Curriculum Alignment To Ensure The Achievement Of The Teacher's Graduation Profile“ - Tacilla Ramirez, Nancy Jesús (2022)
“Initial teacher training is recognized as one of the fundamental factors to improve the quality of educational processes in the classroom, therefore, it is relevant to ensure that future teachers acquire the disciplinary and pedagogical skills necessary for the exercise of a teaching practice appropriate to the diversity. In this sense, the purpose of this study was to analyze the curricular alignment process of the Initial Teacher Training (FID) curriculum for primary education in the training proposal of an Institute of Higher Pedagogical Education. The approach that is assumed is qualitative with a phenomenological design, which allows the description and interpretation of the incorporation and approach of the National Basic Curriculum Design (DCBN) of the FID in the levels and processes of management through documentary analysis and interviews that collect the experiences of the participants. The research made it possible to describe the meaning and specific character of the curricular alignment processes, the implications of assuming the transversality of research and pre-professional practice, and the relevance of integrative projects in the articulation of the curriculum and the improvement of the efficiency of initial teacher training in terms of skills development. Experience reveals that. to improve the coherence between the initial teacher training curriculum and the pedagogical practice aimed at achieving the teacher's graduation profile. Permanent reflection by the educational community and continuous improvement of their skills is required.“